Snow White and the Seven Dwarfs - Walt Disney Home Video (Firm); Walt Disney Company (Burbank, Calif., 2009)
A young princess goes into hiding with seven dwarfs when her stepmother tries to murder her, and then she meets her Prince Charming.
Keywords: Snow White (Tale); Video recordings; Fairy tales; Film adaptations